Hi andrew , for these question, Can I simplify or didn't use to add the calculation steps? I think I can't simplify it ,because the question asked to use the substitution method.

The solution for 5x = y + 6, 2x - 3y = 4 is x = 14/13, y = -8/13. From 5x = y + 6 , we can get y = 5x - 6, which we can put it into the 2th equation. 2x - 3y = 4 2x - 3 (5x - 6) =4 -13x + 18 =4 x = 14/13

put x = 14/13 into the y = 5x - 6 , we can get the value of y y= 5x - 6 y= 5*14/13 - 78/13 y= 70/13-78/13 y= - 8/13

There are no comments.